Characteristics of adults who reported not having had COVID-19 in Spain after the first two years of the pandemic and associated factors - María Teresa Beca-Martínez; Alba Ayala; María Falcón-Romero; Carmen Rodríguez-Blázquez; Agustín Benito-Llanes; Maria João Forjaz; María Romay-Barja (Elsevier, 2024)
Background: There is little evidence regarding the characteristics of adults who self-reported not having had COVID-19 after two years of the pandemic. This study aimed to analyse the characteristics of no-COVID-19 respondents and the associated factors to better understand which may have conditioned not having had the disease as guidance to help in the design of better public health strategies. Methods: This cross-sectional, observational study was conducted in the Spanish general population in a representative sample of 1051 adults who completed an online survey in September 2022. Multivariable logistic regression was performed to assess which factors were related to reporting not having had COVID-19. Results: Almost half of the respondents (47.8%) reported not having ever had COVID-19. Significant differences were found between people who reported having had and not having had COVID-19 according to sex, age, education level, employment and living with children. No-COVID-19 respondents had greater concern and less fear of the disease and were more worried about the new variants. After the multivariable analysis, factors associated with no-COVID-19 respondents were male sex (OR)=1.40; 95% (CI=1.07-1.82), older age (OR=1.01; 95% CI=1.01-1.03), having a greater perception of disease severity if infected (OR=4.71; 95% CI=2.97-7.47), greater adherence to preventive measures (OR=1.02; 95% CI=1.01-1.03), and having received a complete vaccination schedule and booster dose (OR=1.56; 95% CI=1.03-2.36). Conclusions: Analysing the characteristics of people reporting not having had COVID-19 can support public health decision-makers in designing better interventions and facilitating the implementation of effective prevention and control measures to prepare for and respond to a possible future pandemic.